1997
DOI: 10.1093/emboj/16.16.4951
|View full text |Cite
|
Sign up to set email alerts
|

Association of muscle-specific kinase MuSK with the acetylcholine receptor in mammalian muscle

Abstract: During synaptogenesis at the neuromuscular junction, a neurally released factor, agrin, causes the clustering of acetylcholine receptors (AChRs) in the muscle membrane beneath the nerve terminal. Agrin acts through a specific receptor which is thought to have a receptor tyrosine kinase, MuSK, as one of its components. In agrin‐treated muscle cells, both MuSK and the AChR become tyrosine phosphorylated. To determine how the activation of MuSK leads to AChR clustering, we have investigated their interaction in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
130
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 58 publications
(92 reference statements)
10
130
1
Order By: Relevance
“…Potentially, protein interactions underlying localization could be regulated via posttranslational modifications of the AChR, rapsyn, or additional binding proteins. Consistent with the first possibility, agrin/MuSK signaling induces rapid tyrosine phosphorylation of the AChR β and δ subunits , Mohamed et al, 2001, mediated by an intervening cytoplasmic tyrosine kinase (Fuhrer et al, 1997), perhaps of the src and/or abl families Swope, 1999, Finn et al, 2003). Phosphorylation correlates closely with reduced mobility and detergent extractability of the AChR (Meier et al., 1995, Borges andFerns, 2001), suggesting that it regulates linkage to the cytoskeleton.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Potentially, protein interactions underlying localization could be regulated via posttranslational modifications of the AChR, rapsyn, or additional binding proteins. Consistent with the first possibility, agrin/MuSK signaling induces rapid tyrosine phosphorylation of the AChR β and δ subunits , Mohamed et al, 2001, mediated by an intervening cytoplasmic tyrosine kinase (Fuhrer et al, 1997), perhaps of the src and/or abl families Swope, 1999, Finn et al, 2003). Phosphorylation correlates closely with reduced mobility and detergent extractability of the AChR (Meier et al., 1995, Borges andFerns, 2001), suggesting that it regulates linkage to the cytoskeleton.…”
mentioning
confidence: 76%
“…MuSK-induced phosphorylation of the AChR β and δ subunits involves an intervening cytoplasmic tyrosine kinase (Fuhrer et al, 1997), whose activity and/or localization appears to be rapsyn-dependent Swope, 1999, Mittaud et al, 2001). Indeed, agrininduced phosphorylation of the AChR is significantly decreased in rapsyn null myotubes (Apel et al, 1997) and rapsyn activates cytoplasmic kinases in heterologous cells (Qu et al, 1996, Mohamed andSwope, 1999).…”
Section: Phosphorylation Of Achr β and δ Subunitsmentioning
confidence: 99%
“…It has been shown that MuSK is a critical component of the functional receptor for agrin (Glass & Yancopoulos 1997). Although MuSK itself fails to bind agrin directly, the kinase activity and the extracellular domain of MuSK are required for both the phosphorylation and cluster formation of the acetylcholine receptor (Fuhrer et al 1997;Glass & Yancopoulos 1997). Thus, it is also possible that the Ror-family RTKs are also components of functional receptors for particular ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins are associated with nAChR, including rapsyn, which mediates the association of the receptor to the cytoskeleton (18 -20). Protein tyrosine phosphorylation mediates the cytoskeletal anchoring of the receptor (21,22), and SFK are involved in this phosphorylation (23). Inhibition of Src increases the response of the receptor, and vice versa, when Src is highly activated the receptor activity is inhibited (24).…”
mentioning
confidence: 99%